2013
DOI: 10.3389/fmicb.2013.00331
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of survival, responses and sources of Salmonella in low-moisture environments

Abstract: Some Enterobacteriaceae possess the ability to survive in low-moisture environments for extended periods of time. Many of the reported food-borne outbreaks associated with low-moisture foods involve Salmonella contamination. The control of Salmonella in low-moisture foods and their production environments represents a significant challenge for all food manufacturers. This review summarizes the current state of knowledge with respect to Salmonella survival in intermediate- and low-moisture food matrices and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
162
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(180 citation statements)
references
References 108 publications
2
162
0
2
Order By: Relevance
“…According to Finn et al [5], bacteria have osmoprotectants which aid in bacterial survival in low environments. The function of osmoprotectants is to balance the osmolarity within the bacterial cell to that of the external environment to avoid any loss of water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Finn et al [5], bacteria have osmoprotectants which aid in bacterial survival in low environments. The function of osmoprotectants is to balance the osmolarity within the bacterial cell to that of the external environment to avoid any loss of water.…”
Section: Resultsmentioning
confidence: 99%
“…However, many studies done by researchers in literature have found that microorganisms have the capability of surviving in low foods [1,5]. The increased number of food-borne related illness outbreaks recently, associated with low foods, has portrayed that even though microorganisms cannot proliferate in such foods, there is a likelihood for them to be persistent for extended periods of time [1,5,6]. Depending on the type of microorganism, they can cause illness even with their low infectious dose or subsequent temperature abuse that permits the growth of these microorganisms [5].…”
Section: Introductionmentioning
confidence: 99%
“…Future systematic studies over periods of time should analyze the factor ''flourmill'' in a systematic way, together with the hygienic and technological conditions. Food business operators producing foodstuff containing uncooked flour should be aware of the possibility of the presence of STEC and should consider the higher thermal stability of STEC in products with low water activity (Finn et al 2013;Liu et al 2014;Knödler et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic Enterobacteriaceae may occur in products with low water activity (a w ) and that exhibits higher heat tolerance (Gilbert et al 2010;Finn et al 2013;Beuchat et al 2013). Thermal inactivation of STEC in low moisture foods requires higher temperatures and is strain dependent (Liu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation